Colors, words, sounds, space, time: “total work of art” - Fariña Busto, María José (2019)
This article gives a vision of the concept of “total work of art” from the point of view of certain artists and historians who developed their works and ideas between the end of the 19th century and the first decades of the 20th century. Therefore, this research is based on the conceptions about art and the various arts had some of them, establishing the relation between the material and the materials from which the work is materialized in each one of them.